Sodium Modeling to Reduce Intradialytic Hypotension during Haemodialysis for Acute Kidney Injury in the Intensive Care Unit - Lynch, Katherine E. (Nephrology (Carlton), 2016)
AIM: Intradialytic hypotension often complicates haemodialysis for patients with acute kidney injury (AKI), and may impact renal recovery. Sodium modeling is sometimes used as prophylaxis against intradialytic hypotension in the chronic haemodialysis population, but there is little evidence for its use among critically ill patients with AKI. METHODS: A retrospective cohort with AKI requiring intermittent haemodialysis in the intensive care unit from 2001–2008 was used to study the association of prophylactic sodium modeling and multiple outcomes. Outcomes included a composite of in-hospital death or dialysis dependence at hospital discharge, as well as intradialytic hypotension, ultrafiltration goal achievement, and net ultrafiltration volume. Associations were estimated using logistic regression, mixed linear models, and generalized estimating equations adjusting for demographic and clinical characteristics. RESULTS: 191 individuals who underwent 892 sessions were identified; sodium modeling was prescribed in 27.1% of the sessions. In adjusted analyses, sodium modeling was not significantly associated with intradialytic hypotension (p=0.67) or with the ultrafiltration goal achievement (p=0.06). Sodium modeling during the first dialysis session was numerically associated with lower risk for the composite of in-hospital death or dialysis dependence: adjusted OR (95% CI) 0.39 (0.15–1.02; p=0.06); however, this association did not reach statistical significance. CONCLUSION: We did not observe statistically significant associations between sodium modeling and improved outcomes among AKI patients receiving intermittent dialysis in the intensive care unit. However, suggestive findings warrant further study.